2004
DOI: 10.1097/01.ccm.0000126264.00551.c8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia exposure impairs surfactant function and metabolism

Abstract: Oxidative stress on the endogenous surfactant system may represent an important mechanism contributing to the surfactant dysfunction and abnormal surfactant metabolism associated with hyperoxia-induced lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
1
25
0
2
Order By: Relevance
“…Consistent with previous reports [22], our data showed that prolonged exposure to hyperoxia resulted in decreased compliance and increased inflammation within the lung, which was associated with increased levels of oxidative markers and an alteration in antioxidative metabolism. A unique aspect of our study was the detailed analysis of the surfactant system, specifically oxidized surfactant, at 2 different time points over the course of the injury.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Consistent with previous reports [22], our data showed that prolonged exposure to hyperoxia resulted in decreased compliance and increased inflammation within the lung, which was associated with increased levels of oxidative markers and an alteration in antioxidative metabolism. A unique aspect of our study was the detailed analysis of the surfactant system, specifically oxidized surfactant, at 2 different time points over the course of the injury.…”
Section: Discussionsupporting
confidence: 94%
“…We consider the increased LA PL levels to most likely reflect a protective measure involving enhanced surfactant secretion because it appears unlikely that LA to SA subtype conversion would be decreased in the presence of increased serum proteins within the airspace [29]. In fact, based on the present findings, we suspect that the increased serum protein levels present within the lungs of the 60-hour exposure group may have inhibited the function of surfactant LA, thereby providing the major contribution to the decreased lung compliance observed in these animals [22]. Similar observatrions were made by Dombrowski and colleagues [25].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Ample literature is available that indicates breathing 100% oxygen may impair pulmonary gas exchange due to inhibition of hypoxic pulmonary vasoconstriction (38) and resorption atelectasis (38,39) in lung regions with low ventilation/perfusion ratios (40). Moreover, hyperoxic ventilation combined with high tidal volumes caused lung injury (41), similar to the damage induced by prolonged hyperoxia (Ͼ48 hrs) (42). This striking discrepancy may be due to our ventilator protocol, that is, application of PEEP levels of 12 production (open whiskers) and direct, aerobic glucose oxidation (hatched whiskers) in the control (white symbols, n ϭ 10) and hyperoxic (gray symbols, n ϭ 10) animals.…”
Section: Discussionmentioning
confidence: 84%
“…Unlike SP-D ϩ/ϩ animals, SP-D Ϫ/Ϫ mice were able to maintain higher BAL phospholipid levels, phospholipidassociated SP-B, and surfactant function early in hyperoxic exposure. Several previous studies have shown that exposure of rodents to either prolonged periods of hyperoxia or to oxidizing agents such as paraquat to induce a relatively severe oxidative insult resulted in significant lung dysfunction that was associated with oxidative changes in endogenous surfactant (29,37,50,68) and depletion of surfactant phospholipid and surfactant proteins (35). Instillation of exogenous surfactant has been shown to attenuate the degree of alveolar injury caused by hyperoxia resulting in improved survival (51).…”
Section: Ablation Of the Sp-d Gene Results In Progressive Alveolar Prmentioning
confidence: 99%